2009
DOI: 10.1177/0269215508101736
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intervention in brain injury: a pilot randomized study of Tai Chi Qigong

Abstract: Objective: To examine the effects of a brief Tai Chi Chuan Qigong ('Qigong') exercise intervention on individuals with traumatic brain injury. Design: A single-centre randomized controlled trial pilot study. Setting: A registered charity day centre in the community.Subjects: Twenty individuals with traumatic brain injury. Intervention: Intervention participants attended a Qigong exercise session for one hour per week over eight weeks.Control participants engaged in non-exercise-based social and leisure activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(114 citation statements)
references
References 27 publications
4
110
0
Order By: Relevance
“…One of the most notable improvements was with general mood. These findings are similar to those of Blake and Batson, 28 who conducted an eight-week qigong intervention in a nonmilitary population of individuals with TBI. In this British pilot study, the investigators concluded that individuals who participated in eight weeks of qigong instruction reported improvements in their overall mood as well as self-esteem.…”
Section: Discussionsupporting
confidence: 86%
“…One of the most notable improvements was with general mood. These findings are similar to those of Blake and Batson, 28 who conducted an eight-week qigong intervention in a nonmilitary population of individuals with TBI. In this British pilot study, the investigators concluded that individuals who participated in eight weeks of qigong instruction reported improvements in their overall mood as well as self-esteem.…”
Section: Discussionsupporting
confidence: 86%
“…In a pilot unblinded RCT, Blake and Batson [51] examined the effects of an 8-week Tai Chi Qigong intervention; Tai Chi Qigong is a form of Tai Chi that has fewer physical and cognitive demands than ordinary Tai Chi. Participants with TBI at a day center were randomly assigned using a computer-generated random number table to receive the intervention (n = 10) or to a control group (n = 10).…”
Section: Tai Chimentioning
confidence: 99%
“…There were no significant between-group differences in self-reported and familyreported measures of physical functioning, flexibility, selfesteem, and social support for exercise habits. The study only reported on the immediate effect of the intervention and did not assess long-term effects [51]. Larger, more rigorous clinical trials are needed to fully explore the potential benefits of Tai Chi in individuals with TBI.…”
Section: Tai Chimentioning
confidence: 99%
“…Controlled breathing and concentration can result in greater body awareness [23,28,29]. Improvements in perceived self-efficacy have been observed in both older populations [22,30] and clinical populations [31] and this is significant since self-efficacy may influence participation and exercise adherence [22].…”
mentioning
confidence: 99%